Global Price Fixing - Connor, John M. (Studies in Industrial Organization,, 2007)
The book describes and analyzes the formation, operation, and impacts of modern global cartels. It provides a broad picture of the economics, competition law and history of international price fixing. A deeper understanding of the phenomenon is afforded by intensive case studies of collusion in the markets for lysine, citric acid, and vitamins. Particular attention is given to the economic injuries sustained by the cartels' customers. The author assesses whether antitrust enforcement by the European Union, the United States, and other countries is capable of deterring cartels in the foreseeable future.